PP.02.38: THE EFFECTS OF CHRONIC EXERCISE ON BODY COMPOSITION, HEMODYNAMIC PARAMETERS AND MICROVASCULAR REACTIVITY IN YOUNG HEALTHY MEN. (June 2015) - Stupin, M.; Cavka, A.; Rasic, L.; Cosic, A.; Drenjancevic, I.
Abstract : Objective: The aim of our study was to evaluate: 1) how chronic exercise (CEX) modulate body composition components, 2) how CEX affects microvascular reactivity of skin microcirculation (indicator of endothelial function) and 3) is there an association between body composition components and microvascular reactivity in young healthy men. Design and method: Young healthy lean sedentary subjects (SS) (N = 8) and trained athletes (TR) (N = 16) participated in this study. Blood pressure, heart rate, body mass index (BMI), waist to hip ratio (WHR), fasting lipid panel, plasma glucose and C reactive protein (CRP) were measured in all subjects. Body composition was measured with a four-terminal portable impedance analyzer (Maltron Bioscan 920-II). Empirically derived formulas were used to calculate estimated Fat Mass, Muscle Mass, Total Body Water (TBW), Intra-Cellular Water (ICW) and Extra-Cellular Water (ECW). Skin microvascular post occlusive reactive hyperemic (PORH) blood flow was assessed by laser Doppler flowmetry (LDF). Results: All subjects were normotensive, lean, age-matched males, with no difference in BMI, WHR, arterial blood pressure and heart rate, just as in fastig lipid panel, plasma glucose and CRP between SS and TR. Fat Mass% was significantly higher in SS than in TR (Fat Mass% SS 13.8 ± 4.2 vs. TR 8.7 ± 1.2, P = 0.012), while Muscle Mass% was significantly higher in TR than in SS (Muscle Mass% SS 45.8 ± 1.5 vs. TR 48.4 ± 1.4, P = 0.022). TBW% was significantly higher in TR when compared to SS (TBW% SS 61.6 ± 3.3 vs. TR 65.8 ± 1.6, P = 0.017), without the difference in specific water compartments (ECW% and ICW%) between groups. Skin microvascular PORH was significantly higher in TR compared with SS (R-O SS 85.5 ± 19.2% vs. TR 125.1 ± 37.4%, P = 0.005). Multiple linear regression results indicate that among body composition parameters only TBW% is significantly assocciated with skin microvascular PORH (P = 0.035). There was no correlation between arterial blood pressure and TBW% in normotensive normaly hydrated subjects. Conclusions: The principle findings of our study are: 1) when trained athletes exibits significantly better skin microvasular reactivity compared to age-matched and physical constitution-matched sedentary subjects, which presupposes better endothelial function; and 2) TBW% may be a associated with vascular reactivity in normaly hydrated normotensive subjects.